MARITIME 4.0 AND EXPECTATIONS IN MARITIME SECTOR - Dursun Balkan (Akademik İncelemeler Dergisi)
As the rapid development of communication and information technologies allows real-time transmission of information, the world is increasingly becoming a global society. In this context, the most developed countries are required to develop their own strategies to encourage the industrial sector to stay up to date and compete in a dynamic and volatile global market in order to maintain its competitive capacity. For this reason, since the path of competitiveness through technological differentiation in industrialization provides a wider and innovative field of research, it reveals the result of a new phase of organization and industrial technology that is beginning to change our relationship with industry, society and human interaction in the business world at present standards. The main target of this study is to reveal the effects of Industry 4.0 on the Maritime sector using with the explanation of the historical development and conceptual framework of today's high technology industry 4.0 and its expectations in maritime sector in the light of the relevant literature. The whole worldwide maritime applications and their reflections on all fields are also the scope of this study. A qualitative descriptive analysis method was conducted to determine the current situation of Maritime Sector which is including Industry 4.0 processes. The findings of this study are Marine-related organizations should be reshaped to meet the needs of the future. Measures and regulations related to the increasing environmental protection sensitivity in the world will directly affect almost every area of the sector. Also, the developing technologies, increasing customer demand and intense competition; it will make the recently introduced Industry 4.0 implementation inevitable.